EFFECTS OF PROBIOTIC SUPPLEMENTATION ON INDUCING REMISSION TO DRUG-FREE NORMOGLYCEMIA IN ADULTS WITH PREDIABETES – STUDY DESIGN. - Sultan, Farah (My University, 2017)
BACKGROUND: Patients with prediabetes are at a high risk of developing type 2 diabetes (T2D) and the current strategies to prevent the progression of prediabetes to T2D are difficult to implement at the population level. Recently, the role of gut microbiota has emerged as a possible link to metabolic disease. The modulation of the gut microbiota in individuals with prediabetes through probiotic supplementation may improve metabolic dysfunction and induce remission of prediabetes to normoglycemia. OBJECTIVES: The primary objective of this trial is to determine the effect of 900 billion CFU/day of VSL#3®, a multi-strain probiotic supplement for 20 weeks, on induction of drug-free remission to normoglycemia (HbA1c<6.0%) in adults with prediabetes compared to placebo 20 weeks post-randomization. METHODS: In a randomized, triple-blind, controlled multi-centre trial, 568 adults with prediabetes will undergo a 2-week run-in after which they will be randomly allocated to 20 weeks of either 900 billion CFUs of VSL#3® per day or placebo. Prediabetes remission will be measured using HbA1C at week 20 and 32. Change in insulin resistance (HOMA-IR), beta-cell function (HOMA-B), weight, BMI, waist circumference and fecal relative abundance of bacteria will be measured from baseline at week 20 and 32. Exploratory regression analyses will involve a multiple logistic regression model to assess whether the change in relative abundance of the Rosburia genus from baseline at week 20 is an independent predictor of drug-free prediabetes remission at week 20. DISCUSSION: Individuals with prediabetes are at high risk of developing T2D and the induction of prediabetes remission would be important to patients and clinicians. The role of microbiota in metabolic processes presents the potential for therapeutic applications of probiotics. If successful, probiotics would offer a therapeutic option for reversing prediabetes to normoglycemia that is simple, cheap and easy to incorporate into standard clinical care.
Study design of a randomized-controlled trial investigating the effects of probiotic supplementation on induction of prediabetes remission to normoglycemia in adults with prediabetes.
Keywords: study design; protocol; randomized controlled trial; diabetes; probiotics